2016
DOI: 10.1097/md.0000000000003051
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Therapy and Viral Suppression Among Foreign-Born HIV-Infected Persons Receiving Medical Care in the United States

Abstract: Immigrants to the United States are more likely to be diagnosed with human immunodeficiency virus (HIV) infection compared with native-born persons. Navigating access to healthcare in the United States can be challenging for foreign-born persons, and HIV treatment outcomes may be suboptimal for these persons. We compared characteristics of and assessed disparities in clinical outcomes of foreign-born persons in care for HIV in the United States.The Medical Monitoring Project is a complex sample, cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…However, after non-U.S.-born Black adults receive HIV diagnosis and access HIV medical care, they are as likely as U.S.born Black adults to be engaged and to be retained in HIV-related medical care after diagnosis. A recent national study reported no substantial difference in the prevalence ratio of antiretroviral prescription and viral suppression between U.S-born and non-U.S.-born persons with an HIV diagnosis [8].…”
Section: Discussionmentioning
confidence: 96%
“…However, after non-U.S.-born Black adults receive HIV diagnosis and access HIV medical care, they are as likely as U.S.born Black adults to be engaged and to be retained in HIV-related medical care after diagnosis. A recent national study reported no substantial difference in the prevalence ratio of antiretroviral prescription and viral suppression between U.S-born and non-U.S.-born persons with an HIV diagnosis [8].…”
Section: Discussionmentioning
confidence: 96%
“…Meanwhile, in a study by the British Columbia Centre for Excellence in HIV/AIDS which investigated treatment outcomes among those who initiated cART at high CD4 cell count, 80% of study participants were male. Similarly, male represent 71.6% of PLHIV in the study of cART and viral suppression among immigrants in the US 23 . The exposure category of the heterosexual is considered the main mode of HIV transmission in Yemen as seen in most countries.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was not anticipated because non-U.S.-born populations typically have been disproportionally lacking health coverage and receive fewer medical services than U.S.-born persons [ 8 ]. An examination of healthcare coverages demonstrated that a substantially higher proportion of non-U.S.-born persons were uninsured and received Ryan White HIV/AIDS Program (RWHAP) assistance, compared with U.S.-born persons receiving HIV infection-related medical care [ 19 ]. RWHAP provides services for persons living with HIV who are uninsured [ 20 ] and offsets the lack of healthcare coverage that would otherwise have hindered linkage to HIV care and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous reports on viral suppression are mixed. In one study, non-U.S.-born persons in the Caribbean region achieved almost similar viral suppression, compared with U.S.-born persons (73.4% versus 73.3%) and lower viral suppression, compared with non-U.S.-born persons from Africa (73.4% versus 78.3%) [ 19 ]. Another study reported substantial differences between U.S.-, African-, and Caribbean-born persons with HIV infection in 2009 by using a national representative sample in which Caribbean-born persons achieved substantially less viral suppression than African- or U.S.-born persons [ 28 ].…”
Section: Discussionmentioning
confidence: 99%